Pemberdayaan Karang Taruna menjadi Sentra Produksi Tepung Pisang Berbasis Ekonomi Kerakyatan - Rate, Suherman; Dewanti, Ritma; Dahro, Ahmad; Ishak, Syamsopyan; Rinjani, Margareta (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The regional economy can improve if existing local potential can be developed optimally. The implementation of this community service is training in skills to make banana flour and then process it into food products that are expected to have economic value. The partner in this program is the Tanjung Agung Village Youth Organization which has 25 members. The results of the implementation of Community Service, of the 25 youth organizations who took part in the training, before the training was carried out, all participants did not know the process of making banana flour and processed banana flour products. However, after the training was carried out, all participants were able to know how to make banana flour and processed banana flour products. The conclusion of this Community Service is that implementation is by external targets where there are changes in skills after training is carried out.